VALUASI EKONOMI ANACARDIACEAE DI PULAU LOMBOK, INDONESIA - Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Fathurrahman, Fathurrahman (Nusantara Hasana Journal, 2025)
Economic valuation is a calculation of the value of the economic benefits of a resource. Kekait is a village in Gunungsari District, West Lombok Regency, West Nusa Tenggara Province, Indonesia. Lombok Island is included in the Lesser Sunda Islands. Kekait village has a diversity of biological resources, one of which is the Anacardiaceae family. Until now there has been no study that focuses on the economic value of Anacardiaceae in Kekait Village. Therefore, it is necessary to carry out this research which aims to analyze the economic value of Anacardiaceae in Pusuk Lestari Village. The research was carried out using purposive sampling through field observations in the form of species identification and population calculations. Then interviews were conducted with local communities regarding utilization, productivity and periodicity of the harvest period and then the value of the economic benefits was calculated and analyzed descriptively. Based on identification, there are five species of Anacardiaceae family in Kekait Village, namely: Mangifera indica, Mangifera odorata, Spondias dulcis, Anacardium occidentale, and Lannea coromandelica. These five species are economically valuable plants with a total direct economic value of IDR 39,032,244,000.00.